Risk factors for psychopathy in a sample of institutionalized adolescent offenders - Cardoso, Rui (2020)
Introduction: Juvenile delinquency is an increasingly worrying issue in society, assuming increasing visibility and public recognition. Antisocial and persistent behaviour is early revealed in many individuals through certain characteristics that will later lead them to become involved in delinquency, as well as crime in general. So, children and adolescents exhibiting these same characteristics, are seen as socially inadequate, since their mechanisms of interaction and problem solving are also socially inadequate. Various factors such as culture, family socialization practices and the child's temperament may maximize or minimize the probability of such behaviour to occur. It is therefore essential to recognise these risk factors in the lives of these adolescents as early as possible, in an attempt to reduce adult crime. Method: Qualitative study, through the analysis of fourteen cases of institutionalized adolescent offenders, aged between 14 and 17 years. The analysis of the presence of risk indicators for the development of psychopathy, which appear associated with deviant and maladaptive attitudes and behaviours during adolescence, was the main objective. Results: It was found that many of these adolescents have many risk factors for antisocial behaviour that could evolve (e.g., absence of guilt towards their actions, lack of empathy towards the victims, irresponsibility and impulsiveness), which may lead to the rooting of unacceptable norms of social conduct, initiating a delinquent way of life. Discussion and conclusions: The presence of traits of coldness and emotional insensitivity, such as impulsiveness and irresponsibility, as well as the dimensions of grandiosity and manipulation, are shown to be present through the absence of guilt or remorse, absence of empathy and superficial affection, which later in adulthood may give rise to deviant and delinquent behaviour. For a better understanding of the phenomenon, it is expected to identify antisocial behaviours in adolescents through this study, as well as risk factors that demonstrate that specific characteristics may evolve to more serious delinquent behaviours.